Two novel uranyl complexes of a semi-rigid aromatic tetracarboxylic acid supported by an organic base as an auxiliary ligand or a templating agent: an experimental and theoretical exploration12. Issue 15 (21st April 2015) - Zhu, Liu-Zheng; Wang, Cong-Zhi; Mei, Lei; Wang, Lin; Liu, Yun-Hai; Zhu, Zhen-Tai; Zhao, Yu-Liang; Chai, Zhi-Fang; Shi, Wei-Qun
<x xml:space="preserve">Abstract</x> Two novel uranyl complexes were constructed by a semi-rigid aromatic tetracarboxylic ligand.